Subjective Well-Being and Schools in South Africa: A Post-COVID-19 Analysis - Morales-Olivares, Rommy; Aguirre-Nuñez, Carlos; Nuñez-Carrasco, Lorena; Ulloa-León, Felipe (Frontiers in Psychology, 2022)
From the analysis of the Wave 5 National Income Dynamics Study-Coronavirus Rapid Mobile Survey (NIDS-CRAM 2021) dataset in South Africa, we developed a model of analysis based on 3 dimensions, namely: Subjective well-being, Material conditions of existence Importance attributed to education during the Covid-19 pandemic. A cross-sectional analysis of the data for the case of the Gauteng area indicates that the dimension of subjective well-being of families in South Africa - even in relation to factors such as deprivation conditions (e.g. hunger) - does not necessarily influence the importance attributed to education that respondents attach to their children's education, reflected in whether or not they send them to school, but is a predictor of concern about their children's education and future. Our working hypothesis is that, although there is little evidence that subjective well-being has a significant association with respondents' willingness for their children to continue their schooling, there is a significant indirect effect of subjective well-being especially determined by gender, as well as of the material conditions of existence in relation to the greater or lesser importance that respondents attribute to their children's education. Likewise, and in more general terms, subjective wellbeing is related to gender, with women having the lowest levels of subjective wellbeing.